Linking the Narcotics Monitoring System Database to Quantify the Contribution of Prescribed and Non-Prescribed Opioids to Opioid Overdoses in Ontario, Canada. (2018) - Martins, Diana; Singh, Samantha; Khuu, Wayne; Tadrous, Mina; Paterson, Michael; Juurlink, David; Mamdani, Muhammad; Gomes, Tara
No abstract available